Understanding the changes in endogenous GA3 in relation to developmental transitions in cauliflower (Brassica oleracea var. botrytis L.) - Sohamkumar Luhana; Shrawan Singh; Shivani Nagar; Anamika Chandel; Kishor Varotariya; Manisha Mangal; Aditi Kundu; Navinder Saini; Anil Khar (PLoS ONE, 2025)
Cauliflower is a crop with intricate developmental transitions influenced by both external and internal cues. Plant growth regulators (PGRs) play a key role in developmental transitions and plant responses to environmental factors. The present study aimed to investigate the endogenous levels of gibberellins (GAs) (i) at six different developmental stages and (ii) at four time points in four varieties of cauliflower using high-performance liquid chromatography (HPLC). The Pusa Ashwini, Pusa Sharad, Pusa Shukti, and Pusa Snowball Kt-25 varieties represent all four thermosensory-based maturity groups: early (20–27 °C), mid-early (15–20 °C), mid-late (12–16 °C), and late or snowball (10–16 °C), respectively. GA3 content was highest in Pusa Shukti (4.020 ppm) and lowest in Pusa Ashwini (3.091 ppm). A higher endogenous GA3 concentration was recorded at the bolting stage (4.118 ppm), seedling stage (4.057 ppm), and curd initiation stage (3.722 ppm), suggesting its role in stalk elongation. The difference in GA3 content was significant between curd (3.613 ppm) and leaf tissues (2.947 ppm) at the full curd stage and nonsignificant between stalk (3.948 ppm) and leaf tissues (4.118 ppm) at the bolting stage. Regarding the time points, the GA3 content was highest in Pusa Sharad (4.311 ppm) and lowest in Pusa Ashwini (2.990 ppm). GA3 content showed a significant positive correlation with duration to crucial developmental transitions, namely the curd initiation stage, the full curd stage, and the bolting stage. The study highlights the role of endogenous gibberellins in plant development and suggests their potential for benefiting seed production.